2021
DOI: 10.18769/ijasos.876374
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Sustainability Through Covid 19: A Case Study of the Festivals on the Island of Rhodes

Abstract: Cultural heritage is one of the key elements of a region's identity and local culture can be an important asset in an effort to highlight and promote a region with the ultimate goal of sustainable development and prosperity of the local community.Local festivals and celebrations contribute to reducing tensions, overcoming dividing lines, developing reciprocity and respect for diversity. They give participants the opportunity to create bonds of contact and communication, create a "sense of belonging", cross bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Moreover, "I increasingly come across angry people around me, who get involved in quarrels, who talk in a nonsensical manner at my job, in the streets, at the market". Distrust and anger peak in individuals when tolerance for frustration decreases and stress and depression increase, which is confirmed by international research, also in Greece, investigating the psychological impacts of the pandemic (Luo et al, 2020;Marmarosh, 2020;Martinez;2020;Mazza et al, 2020;Parks, 2020;Diamanti, 2021;Fountoulakis, 2021;Giannopoulou et al, 2021;Matzanos & Xanthacou, 2021b;Papavasileiou et al, 2021;Strongylaki, 2021;Xanthacou et al, 2021, among others).…”
Section: Discussion-conclusionmentioning
confidence: 70%
See 1 more Smart Citation
“…Moreover, "I increasingly come across angry people around me, who get involved in quarrels, who talk in a nonsensical manner at my job, in the streets, at the market". Distrust and anger peak in individuals when tolerance for frustration decreases and stress and depression increase, which is confirmed by international research, also in Greece, investigating the psychological impacts of the pandemic (Luo et al, 2020;Marmarosh, 2020;Martinez;2020;Mazza et al, 2020;Parks, 2020;Diamanti, 2021;Fountoulakis, 2021;Giannopoulou et al, 2021;Matzanos & Xanthacou, 2021b;Papavasileiou et al, 2021;Strongylaki, 2021;Xanthacou et al, 2021, among others).…”
Section: Discussion-conclusionmentioning
confidence: 70%
“…Research in different populations and different countries. In addition, negative, the psychological impact is found in Greek data and surveys with empirical evidence in different populations, data influencing life satisfaction (Diamanti & Nikolaou, 2021;Fountoulakis et al, 2021;Giannopoulou et al, 2021;Matzanos & Xanthacou, 2021b;Papavasileiou et al, 2021;Strongylaki, 2021;Xanthacou et al, 2021, among others).…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] state that further research on the relationship between intangible cultural heritage, tourism, and sustainable development is required. A recent, related study on Greece [11] showed that wine tourism could lead to sustainable development in the Peloponnese region, while [12] highlighted the contribution of the Rhodes folk festival to local sustainable development.…”
Section: Introductionmentioning
confidence: 99%